Challenges for sport development: Women's entry level cycling participation. Issue 4 (August 2016) - Rowe, Katie; Shilbury, David; Ferkins, Lesley; Hinckson, Erica
Highlights: Participation is identified as a complex concept that spans several disciplines. Principles of social ecological theory and sport development guide the study. Explores perceived cycling motivations, supports and constraints of beginner females. Identified motivations and barriers provide insights for stakeholders. Further research is needed to inform strategies to address gender disparity in cycling. Abstract: Sport participation is an issue of relevance to sport managers, yet it is an often-neglected area of sport management research. Cycling is a particularly complex form of participation to examine given its many formats, including sport, recreational and commuter cycling, and the multifaceted nature of the cycling landscape involving a broad range of stakeholders. In Australia, women are underrepresented in cycling participation and membership (Australian Bureau of Statistics, 2012; Cycling Australia, 2014 ), yet women show an interest in cycling training courses. The present paper explores motivations, supports and constraints reported by a group of entry-level female cyclists who participated in a training programme accredited by AustCycle, an initiative led by Cycling Australia. We draw on a health and sport development driven framework, informed by social ecological theory (Rowe et al., 2013 ), and suited to examining the issue of women's cycling participation in Australia. Results show that a range of individual characteristics, and factors within the social and physical environment, were perceived by study participants as barriers to participation. Of these, skill level, confidence, traffic/road conditions, and social support networks held particular relevance. Participants also discussed specific cycling barriers and supports of relevance to certain forms of cycling. Preliminary insights into perceptions held by a group of entry-level female cyclists highlight overlaps between cycling formats and indicate that conceptual advancements in the development of sport, and development through sport could be collectively considered in the context of women's cycling participation. Further research opportunities were also identified.